Undifferentiated Pleomorphic Sarcoma Presenting as Abdominal Pain with a Pulsatile Mass. (3rd August 2016) - Moradi, Arash; Afsharfard, Abolfazl; Atqiaee, Khashayar
Abstract : Malignant fibrous histiocytoma (MFH) is a rare tumor that mostly involves adults aged 50 to 70. The most common anatomic location is the lower extremities. MFH of the retroperitoneum usually manifests late in its course and may be initially mistaken with other more common diagnosis. Here, the authors describe a 60-year-old man that was brought to the emergency department with a chief complaint of periumbilical abdominal pain. Our patient presented with symptoms consistent with a symptomatic aortic aneurysm, but a mass was encountered during surgery. In such circumstances the diagnosis of malignant sarcoma must be kept in mind and attempts at full resection with tumor-free margins are necessary.